Nilai-Nilai Ajaran Agama Islam Dalam Tarian Saman Gayo - Wirman Tobing; M. Agung Hanafi; Alpahmi Husaini; MHD. Ad-Durrun Nafis; Indah Lestari (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
Analysis Of Values In Saman Dance, June 2021. His study aims to analyze values contained of art Saman Dance. Saman Dance from the Tribe Gayo in Central Aceh, the Tribe Alas in Southeast Aceh (Blangkejeren), and East Aceh. The method used in this research is a method of analytical descriptive. In this method research data be examined to be the lesson. As for data collection techniques used in this research was the literature study and observation. The analysis shows that contained in a Saman Dance various value, of them religious values, ethics value, and social value. The value of the debt reflected of a whole art Saman Dance, start of the exercises/preparation, movements dance, singing, and the words/poetry. Keywords: Aceh, Ethics, Religious, Social, Saman Dance